SISTEM PENANDAAN TOKOH GANA PADA CANDI BUDDHA DI JAWA TENGAH - Sarjanawati, Rr. Sri Wahyu (Forum Ilmu Sosial, 2009)
Temple as a Ã‚Â result of culture during Hindu-Buddha Ã‚Â is a building depicting cosmogony concept.Ã‚Â Despitefully, temple also is Ã‚Â a replica from mount Mahameru residence of the deities. Figure Gana isÃ‚Â one of creature chiseled at temple wall, as complement of depiction of cosmos. Existence of this fgureÃ‚Â at temple contains purposes and objectives. Problem which will be broken, that is: ( 1) How denotingÃ‚Â system of fgure Gana at Ã‚Â temple Borobudur and Ã‚Â temple Mendut? ( 2) How Ã‚Â location denoting systemÃ‚Â of fgure Gana at the temple? This research is focused on the Gana at Borobudur and Mendut temples.Ã‚Â The fgure of Gana is analysed by semiotic approach because by this approach every fgure chiseled atÃ‚Â temple relating to signs: signifer (Ã¢â‚¬ËœpenandaÃ¢â‚¬â„¢) and signifed (Ã¢â‚¬ËœpetandaÃ¢â‚¬â„¢), as according to semiotics studyÃ‚Â coverage. Semiotic analyse to Gana fgure can only be done if various descriptions about its ommissionÃ‚Â have been known. The informations which explain the Gana fgure have gotten from written sources ofÃ‚Â establishment rules and of symbolic meaning on every part of temple made by the architects and priestÃ‚Â alive in theirs days. The research procedure was divided into three phases: preparation, feld study, andÃ‚Â data analysis phase. From the result of this research and the discussion, we know that the depiction ofÃ‚Â Gana fgure at Borobudur and Mendut temples doesnÃ¢â‚¬â„¢t get out from cosmogony concept. Depiction systemÃ‚Â of Gana fgure was adapted by symbolic meaning on every parts of temple. So, it can be said that GanaÃ‚Â is an icon from a religious situation during Hindu-budha and a symbol from Ã¢â‚¬Å“upper worldÃ¢â‚¬Â (heaven).Ã‚Â The location of Gana fgure at temple is becaming an icon from cosmogony concept.Keywords: Gana, temple, semiotic.